2019
DOI: 10.1016/j.actbio.2019.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophobic and antimicrobial dentin: A peptide-based 2-tier protective system for dental resin composite restorations

Abstract: Dental caries, i.e., tooth decay mediated by bacterial activity, is the most widespread chronic disease worldwide. Carious lesions are commonly treated using dental resin composite restorations. However, resin composite restorations are prone to recurrent caries, i.e., reinfection of the surrounding dental hard tissues. Recurrent caries is mainly a consequence of waterborne and/or biofilm-mediated degradation of the tooth-restoration interface through hydrolytic, acidic and/or enzymatic challenges. Here we use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
58
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 76 publications
0
58
0
Order By: Relevance
“…While some antimicrobials are known to lose their activity after immobilization [35], we have previously shown that L-GL13K peptides retained activity after covalent immobilization on titanium [36] and after electrostatic adsorption on etched HA discs even after extensive washing and ultrasonication [22]. This property is shared with other antimicrobial peptides [37].…”
Section: Discussionmentioning
confidence: 80%
See 4 more Smart Citations
“…While some antimicrobials are known to lose their activity after immobilization [35], we have previously shown that L-GL13K peptides retained activity after covalent immobilization on titanium [36] and after electrostatic adsorption on etched HA discs even after extensive washing and ultrasonication [22]. This property is shared with other antimicrobial peptides [37].…”
Section: Discussionmentioning
confidence: 80%
“…We developed a long-acting antibiofilm and hydrophobic dentin coating technology using potent and cytocompatible AAMPs to resist recurrent caries at dentin-composite interfaces [22] and here, our main goal was to determine the effects of the AAMP coatings on the microbiome of oral biofilms and their effectiveness at ex vivo dentin-composite interfaces. Noteworthy, we studied the physico-chemical prosperities of all the aforementioned peptides in a preceding manuscript [23].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations